A single Caenorhabditis elegans Golgi apparatus-type transporter of UDP-glucose, UDP-galactose, UDP-N-acetylglucosamine, and UDP-N-acetylgalactosamine. - Caffaro, C; Luhn, K; Bakker, H; Vestweber, D; Samuelson, J; Berninsone, P; Hirschberg, C (2008)
The genome of Caenorhabditis elegans encodes for 18 putative nucleotide sugar transporters even though its glycome only contains 7 different monosaccharides. To understand the biological significance of this phenomenon, we have begun a systematic substrate characterization of the above putative transporters and have determined that the gene ZK896.9 encodes a Golgi apparatus transporter for UDP-glucose, UDP-galactose, UDP- N-acetylglucosamine, and UDP- N-acetylgalactosamine. This is the first tetrasubstrate nucleotide sugar transporter characterized for any organism and is also the first nonplant transporter for UDP-glucose. Evidence for the above substrate specificity and substrate transport saturation kinetics was obtained by expression of ZK896.9 in Saccharomyces cerevisiae followed by Golgi enriched vesicle isolation and assays in vitro. Further evidence for UDP-glucose transport was obtained by expression of ZK 896.9 in Giardia lamblia, an organism recently characterized as having endogenous transport activity for only UDP- N-acetylglucosamine. Expression of ZK896.9 was also able to correct the phenotype of a mutant Chinese ovary cell line specifically defective in the transport of UDP-galactose into the Golgi apparatus and of a mutant of the yeast Kluyveromyces lactis specifically defective in the transport of UDP- N-acetylglucosamine into its Golgi apparatus. Because up to now all three other characterized nucleotide sugar transporters of C. elegans have been found to transport two or three substrates, the substrate specificity of ZK896.9 raises questions as to the evolutionary ancestry of this group of proteins in this nematode.